Effect of iron loading on the photocatalytic performance of Bi2WO6 photocatalyst - Sriwichai,S. (Academic Press Inc., 2015)
© 2014 Elsevier Ltd. All rights reserved. Pure Bi2WO6 and nominal 0.1-2.0 mol% Fe-loaded Bi2WO6 samples were synthesized by hydrothermal method. All samples were characterized in order to obtain the correlation between structure and photocatalytic properties by X-ray diffraction, UV-vis diffuse reflectance spectrophotometry, Brunauer, Emmett and Teller-specific surface area, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, photoluminescence spectroscopy and inductively coupled plasma-optical emission spectroscopy. Photocatalytic activities of all photocatalyst samples were examined by studying the degradation of methylene blue under visible light irradiation. The 0.5 mol% Fe-loaded Bi2WO6 had the best activity in photodegradation of MB in aqueous solution under visible light irradiation. The high performance of Fe-loaded Bi2WO6 could be attributed to the fact that the Fe ions could act as electron traps promoting the electron-hole separation then enhancing the photocatalytic reaction.